2023
DOI: 10.1371/journal.pone.0292498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine consumption combined with listening to music during warm-up on taekwondo physical performance, perceived exertion and psychological aspects

Slaheddine Delleli,
Ibrahim Ouergui,
Hamdi Messaoudi
et al.

Abstract: The effects of caffeine (CAF) and music have been well documented when used separately, but their combined effects are not yet studied. Thus, the present study assessed the acute effects of combining a low dose of CAF with listening to music during warm-up on taekwondo physical performance, perceived exertion (RPE), and psychological responses during taekwondo-specific tasks in male elite athletes. In a double-blinded, randomized, placebo-controlled crossover study design, male taekwondo athletes (n = 16; age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…For warm-up music, recent meta-analysis revealed that this stimulus present greater effects in highly trained subjects than less trained ones regarding psychological responses and the reverse for physical performances 26 . Since participants in the present study are elite athletes, their greater responses to the CAF + M condition may be related to complementary actions by CAF and music at the central and peripheral levels 23 . Specifically, CAF low doses (i.e., ≤ 3 mg .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For warm-up music, recent meta-analysis revealed that this stimulus present greater effects in highly trained subjects than less trained ones regarding psychological responses and the reverse for physical performances 26 . Since participants in the present study are elite athletes, their greater responses to the CAF + M condition may be related to complementary actions by CAF and music at the central and peripheral levels 23 . Specifically, CAF low doses (i.e., ≤ 3 mg .…”
Section: Discussionmentioning
confidence: 88%
“…Recent investigations using males 23 or a mixed sample of taekwondo athletes 20 have reported that combining CAF with other ergogenic aids or other warm-up strategies can result in additive effects on performance beyond that seen when using either strategy in isolation. Since it serves as a psychological ergogenic aid, music has been reported to improve affective balance, behavior, and cognitive skills associated with physical performance enhancement 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine (CAF) is a psychoactive drug capable of enhancing psychological responses [1] as well as physical performance in a variety of exercise and athletic conditions, such as time trials [2], 5 km cycling [3], sprint [4,5], taekwondo-specific agility test [6], and resistance exercise performance [7]. CAF's capacity to bind to adenosine A1A and A2A receptors is most likely responsible for these ergogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, male individuals were predominantly employed in these investigations. Evidently, noticeable variations between the sexes regarding body size, lean body mass, and hormonal activity may influence the ergogenic benefits of the same caffeine dosages [6,14]. Since female participants comprised merely 10% [15], 13% [14], or ~20% [16] of the total number of participants in metaanalyses investigating the ergogenic impact of CAF in several athletic disciplines, it might be hard to generalize the prescription guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…
Caffeine is one of the most commonly consumed drugs in the world and has been used as an ergogenic aid for exercise performance. [1][2][3][4] The effect that caffeine improved exercise performance, showing an increase in cycling time to exhaustion following coffee consumption was first suggested by Costill et al in 1978. 5 A recent metaanalysis demonstrated that caffeine supplementation has positive effects on exercise performance including aerobic
…”
mentioning
confidence: 99%